The Effect of Social Media Marketing Activities on Continuance Intention: A Study of The Brand Fashion Industry - Roni Setiawan; Sekar Wulan Prasetyaningtyas (PT Mattawang Mediatama Solution, 2023)
Recently, both in Indonesia and globally, social media has become increasingly important, especially in the use of the Instagram platform. One of the interesting industries to discuss is the fashion brand industry. The development of fashion is so fast, and along with the increasing use of the Instagram platform in the community, Instagram is a means of selling and promoting fashion products that are marketed to the public. The research that the authors conducted started with the high use of Instagram, the fast development of fashion brands around the world, and their own attractiveness to society. From this phenomenon, the authors have determined the purpose of this study, among others, to find out how Instagram social media marketing activities influence customer satisfaction, perceived value, and repeat purchase intentions. Meanwhile, this study proposes the effect of perceived value on customer satisfaction and repeat purchase intention. The final paper considers the impact of customer satisfaction on repeat purchase intentions. This study uses an online survey of 135 Instagram users who have made purchases online for fashion products to examine the effect of SMMA on perceived value and customer satisfaction. The results of the analysis use partial least squares with smart PLS. Consistent with previous research, only three statements in the hypothesis were accepted, SMMA had a positive effect on CS and PV, then CS had a significant effect on CI, and indirectly, the SMMA variable had a positive and significant impact on CI.